ITGA5 Predicts Dual-Drug Resistance to Temozolomide and Bevacizumab in Glioma - Shi, Ying; Wu, Mengwan; Liu, Yuyang; Hu, Lanlin; Wu, Hong; Xie, Lei; Liu, Zhiwei; Wu, Anhua; Chen, Ling; Xu, Chuan (Frontiers in Oncology, 2021)
Aims Anti-angiotherapy (Bevacizumab) is currently regarded as a promising option for glioma patients who are resistant to temozolomide (TMZ) treatment. But ongoing clinical research failed to meet therapeutic expectations. This study aimed to explore the pivotal genetic feature responsible for TMZ and Bevacizumab resistance in glioma patients. Methods We downloaded the transcriptomic and methylation data of glioma patients from The Cancer Genome Atlas (TCGA), Chinese Glioma Genome Atlas (CGGA), and Gene Expression Omnibus (GEO) databases and grouped these patients into resistant and non-resistant groups based on their clinical profiles. Differentially expressed genes and pathways were identified and exhibited with software in R platform. A TMZ-resistant cell line was constructed for validating the expression change of the candidate gene, ITGA5. An ITGA5-overexpressing cell line was also constructed to investigate its biological function using the CCK8 assay, Western blot, periodic acid–Schiff (PAS) staining, and transcriptional sequencing. Results Change of the cell morphology and polarity was closely associated with TMZ mono-resistance and TMZ/Bevacizumab dual resistance in glioma patients. The expression level of ITGA5 was effective in determining drug resistance and the outcome of glioma patients, which is regulated by methylation on two distinct sites. ITGA5 was augmented in TMZ-resistant glioma cells, while overexpressing ITGA5 altered the cell-promoted TMZ resistance through enhancing vascular mimicry (VM) formation correspondingly. Conclusions Both the epigenetic and transcriptional levels of ITGA5 are effective in predicting TMZ and Bevacizumab resistance, indicating that ITGA5 may serve as a predictor of the treatment outcomes of glioma patients.